Cfa-circ002203 was upregulated in rapidly paced atria of dogs and involved in the mechanisms of atrial fibrosis - Shangguan, Wenfeng; Gu, Tianshu; Cheng, Rukun; Liu, Xing; Liu, Yu; Miao, Shuai; Wang, Weiding; Song, Fang; Wang, Hualing; Liu, Tong; Liang, Xue (Frontiers in Cardiovascular Medicine, 2023)
Background and aims The role of circular RNAs (circRNAs) in the pathophysiology of cardiovascular disease is gradually being elucidated; however, their roles in atrial fibrillation (AF)-related fibrosis are largely unknown. This study aimed to characterize the different circRNA profiles in the rapid-pacing atria of dogs and explore the mechanisms involved in atrial fibrosis. Methods A rapid right atrial-pacing model was established using electrical stimulation from a pacemaker. After 14 days, atrial tissue was collected for circRNA sequencing analysis. In vitro fibrosis was established by stimulating canine atrial fibroblasts with angiotensin II (Ang II). The fibroblasts were transfected with siRNA and overexpressing plasmids to explore the effects of cfa-circ002203 on fibroblast proliferation, migration, differentiation, and the expression of fibrosis-related proteins. Results In total, 146 differentially expressed circRNAs were screened, of which 106 were upregulated and 40 were downregulated. qRT-PCR analysis showed that cfa-circ002203 was upregulated in both in vivo and in vitro fibroblast fibrosis models. The upregulation of cfa-circ002203 enhanced proliferation and migration while weakening the apoptosis of fibroblasts. Western blotting showed that cfa-circ002203 overexpression increased the protein expression levels of fibrosis-related indicators (Col I, Col III, MMP2, MMP9, and α-SMA) and decreased the protein expression levels of pro-apoptotic factors (Bax and Caspase 3) in Ang II-induced fibroblast fibrosis. Conclusion Cfa-circ002203 might serve as an active promoter of the proliferation, migration, and fibrosis of atrial fibroblasts and is involved in AF-induced fibroblast fibrosis.